Exploring Critical Discourse Analysis’s Renowned Studies: Seeking for Aims and Approaches - Nurul Fathia Salma (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2019)
This paper is trying hard to linked all its resources the study conducted by renowned researchers which discuss about Introduction to Critical Discourse Analysis (CDA) where includes the definitions, the manner to do Critical Discourse analysis guided by the established framework. Based on the theories of Michel Foucault, “discourse analysis is focusing on power of relationships in society as expressed by means of language and practices” this study puts its stand of viewpoint. Besides, there are several renowned studies to help understand the principle e.g.,, aims and approaches of CDA. This study believed and stick to the Foucauldian discourse analysis look at how the figures used language to propose their power dominance, and request obedience and honor from those subordinate to them which the are five steps are recommended based on the identification of rules in using